Politics of the Law of Covid-19 Handling by The Indonesian Government from Health Human Rights Perspective - Pertiwi, Analia; Ediyono, Suryo (Department of Civic Education, 2022)
COVID-19 is a disease that was first discovered in China where it spreads very quickly until it was recorded that until January 28, 2021, 1 million Indonesians were exposed to the virus with the highest number of cases in Southeast Asia. Every citizen has the right to be given protection by the government from this case. The right to health is a derivative of human rights that must be protected. In dealing with the COVID-19 pandemic, the government has implemented various legal rules, including government regulations implementing Law Number 1 of 2020, State Finance and Financial System Stability policies during the 2019 Coronavirus Pandemic (COVID-19) and government regulations number 21 of 2020. 2020 is the date of Mass Social Restrictions in the Context of Acceleration (PSBB) for Handling Corona Virus Disease 2019 (Covid-19). The government has also implemented PSBB and Physical Distancing policies, but these policies have not been effective in breaking the chain of transmission of COVID-19. The method used in this study is a descriptive normative juridical research method by providing solutions for handling COVID-19 in Indonesia. This study concludes that the legal politics (PSBB and physical distancing) achieved by the government in handling COVID-19 are not in accordance with Article 28 H paragraphs (1) and 34 of the 1945 Constitution paragraphs (2) and (3).